3D Assembly: Controlled Mechanical Buckling for Origami‐Inspired Construction of 3D Microstructures in Advanced Materials (Adv. Funct. Mater. 16/2016). (April 2016) - Yan, Zheng; Zhang, Fan; Wang, Jiechen; Liu, Fei; Guo, Xuelin; Nan, Kewang; Lin, Qing; Gao, Mingye; Xiao, Dongqing; Shi, Yan; Qiu, Yitao; Luan, Haiwen; et al.
Abstract : On page 2629, Y. Zhang, J. A. Rogers, and co‐workers introduce an approach that exploits controlled mechanical buckling for reversible, autonomic origami assembly of 3D structures across material classes from soft polymers to brittle inorganic semiconductors, and length scales from nanometers to centimeters. This approach provides access to 3D architectures with a broad range of topologies.